SUSTAINABILITY AND EFFICIENCY IN SCHOOL MANAGEMENT: A BIBLIOMETRIC PORTRAIT OF SMART SCHOOL RESEARCH - Syunu Trihantoyo; Guli Ergasheva; Muhamad Sholeh; Amrozi Khamidi; Ainur Rifqi; Ima Widiyanah (Nurul Jadid University, 2026)
The increasing complexity of education management in the digital era poses challenges to achieving sustainability, efficiency, and effective school leadership. The implementation of the smart school concept remains fragmented due to insufficient integration among technological innovation, sustainability, managerial effectiveness, and human resource readiness to support educational transformation. This study aims to map and synthesize research trends in smart school management, with a focus on sustainability and efficiency, during the period 2010–2025. Data obtained from the Scopus database using the keywords “smart school,” “sustainability,” and “efficiency,” resulting in 295 publications analyzed using bibliometric methods using VOSviewer. The results show increased scientific attention since 2018, along with the acceleration of global digitalization in education, with Malaysia, China, India, and Iran as major contributors. Thematic mapping indicates a shift from a technology-based approach to an integrated framework that emphasizes sustainability, efficiency, adaptive leadership, systemic collaboration, learning and innovation, and continuous professional development.